Enhancing Collaborative Web Search with Personalization: Groupization, Smart Splitting, and Group Hit-Highlighting - Morris, Meredith Ringel; Teevan, Jaime; Bush, Steve (Proceedings of CSCW 2008, 2008)
Collaboration on Web search is common in many domains, such as education and knowledge work; recently, HCI researchers have begun to introduce prototype collaborative search tools to support such scenarios. We analyze data from a collaborative search experiment, and based on these data we propose three techniques that can enhance the value of collaborative search tools using personalization: groupization, smart splitting, and group hit-highlighting.